Film As Embodied Art : Bodily Meaning in the Cinema of Stanley Kubrick. - Coëgnarts, Maarten (Boston, MA : Academic Studies Press, 2019)
Film as Embodied Art reveals Stanley Kubrick as a genuine master of the art of embodying themental life of characters, a filmmaker who perhaps more than any otherdirector, uses all the resources of filmmaking in such a controlled and dense manner as to elicit the embodiedconditions necessary to achieve a level of conceptual depth.
Front Cover -- Half-Title Page -- Title Page -- Copyright Page -- Dedication -- Contents -- List of Illustrations -- Acknowledgments -- Introduction The Theoretical Context of This Study -- Chapter 1 Identifying the Meaning: In Search of the Concepts of Kubrick's Films -- Chapter 2 Embodying the Meaning: The Role of Image Schemas, Metaphors, and Metonymies -- Chapter 3 Setting the Conditions of Embodied Meaning-Making in Film: The Role of Film Style and Acting -- Chapter 4 Fleshing Out the Embodied Meaning Visually: The Art of Kubrick -- Chapter 5 Seeing and Listening to Kubrick's Films: The Embodied Film Viewer -- Appendix -- Glossary -- Filmography -- Discography -- Bibliography -- Back Cover.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books